Judgement without Sanction on Corporation's Forest Burning; Judges and In Dubio Pro Natura Principle in Indonesia - Taefur, Mohamad Azkal; Nuriyatman, Eko (UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze judges' decisions related to forest fire cases. More specifically, it seeks to analyze the judges' reasoning based on the principles of justice, legal certainty, and public interest, as well as the application of the principle of in dubio pro natura in environmental damage cases. Forest and land burning for plantation purposes continues to increase, and legal efforts and law enforcement face numerous obstacles in terms of evidence. As a result, many forest and land burning cases go unpunished. The decision No. 233/Pid.b/Lh. 2020/Pn.Pbu and the cassation decision No. 3840 K/Pid.Sus.Lh/2021 acquitted the defendant PT S of liability for the forest and land fire incident. To analyze this case, the study uses Gustav Radbruch's theory of the purpose of law, which includes justice, legal certainty, and utility. The decisions of the first-instance court and the cassation court failed to adequately consider the principles of justice and utility, particularly regarding environmental protection. Although the principle of “in dubio pro natura” was applied, the judges' decision relied more on the logic of legal certainty, which only determines the decision based on evidence presented in court rather than the actual facts on the ground where the forest fire occurred. The principle of precaution was ignored by the defendant and overlooked by the judges.